Education and early career outcomes of second-generation immigrants in France - Christian Belzil; François Poinas (Institute for the Study of Labor (IZA), 2008)
We estimate a flexible dynamic model of education choices and early career employment outcomes of the French population. Individuals are allowed to choose between 4 options: continue to the next grade, accept a permanent contract, accept a temporary contract, or withdraw from the labor force (a residual state). Our analysis focuses on the comparison between French Second-Generation Immigrants whose parents are born in Africa and French-natives. We find that schooling attainments explain around two thirds of the differences in access to early career employment stability. However, one third cannot be linked to observed investment in human capital.
urn:nbn:de:101:1-20081217151
Keywords: I2; 330; Second-generation immigrants; schooling attainments; fixed term employment; Migranten; Generationenbeziehungen; Bildungsniveau; Erwerbsverlauf; Arbeitsverhältnis; Bildungsinvestition; Frankreich